Smart Computing and Informatics Proceedings of the First International Conference on SCI 2016, Volume 1 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Das, Swagatam; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This volume contains 74 papers presented at SCI 2016: First International Conference on Smart Computing and Informatics. The conference was held during 3-4 March 2017, Visakhapatnam, India and organized communally by ANITS, Visakhapatnam and supported technically by CSI Division V - Education and Research and PRF, Vizag. This volume contains papers mainly focused on applications of advanced intelligent techniques to video processing, medical imaging, machine learning, sensor technologies, and network security.
Preface -- About the Editors -- Conference Organizing Committee -- Table of Contents -- 74 Chapters -- Author Index.
Keywords: Telecommunication; Quantitative research; Artificial intelligence; Communications Engineering, Networks; Data Analysis and Big Data; Artificial Intelligence